Abstracts of papers presented at Symposium on Antarctic Geology and Solid Earth Geophysics, Oslo, 6-15 August 1970 (SCAR/IUGS, 1970)
Keywords: Antarktis; geofysikk; geologi; konferanse; symposium

The Last of "The Ten". Antarctic Pioneer Still Lives On (Antarctic, 1970)
Publisher: New Zealand Antarctic Society Place: Christchurch
Keywords: Antarktis; Hugh Blackwall Evans; Southern Cross; biografi; ekspedisjonen; ekspedisjoner; oppdagelsesreiser; overvintring

Antarktistraktaten: en ny type internasjonal organisasjon - Engh, Ulf (Stiftelsen, 1970)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk

De konsultative møter under Antarktistraktaten - Hanevold, Truls (Stiftelsen, 1970)
Publication Title: Fridtjof Nansen-stiftelsen på Polhøgda. Studie AA:P
Keywords: Antarktis; jus; politikk

Antarktis uten ispanser - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; geofysikk; geologi

Ønske om fortsatt Antarktis-innsats - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; politikk

Tolv lands polarforskere til Antarktis-møte i Oslo - Lund, Thoralv (Polarposten, 1970)
Keywords: Antarktis; forskning

Glaciological investigations on Deception Island - Orheim, Olav (Antarctic Journal of the United States, 1970)
Keywords: Antarktis; glasiologi

Energetic significance of absorption of solar radiation in polar homeotherms - Øritsland, Nils Are (Antarctic ecology, 1970)
Keywords: Antarktis; fysiologi; seler; stråling; zoofysiologi

The political experiment in Antarctica - Sollie, Finn (Bulletin of the Atomic Scientists, 1970)
General discussion of international cooperation in Antarctica. In special issue Antarctica since the IGY; international laboratory for science and diplomacy.
Publisher: Routledge In special issue Antarctica since the IGY; international laboratory for science and diplomacy. Reprinted in Lewis, Richard S. and Smith, Philip S., eds., Frozen future: a prophetic report from Antarctica, New York, 1973.
Keywords: Antarktis; Antarktistraktaten; internasjonal politikk; internasjonal rett; internasjonal samarbeid